Mapping the types of modularity in open-source hardware. (14th June 2021) - Gavras, Kosmas; Kostakis, Vasilis
Abstract: The importance of intangible code modularity in open-source software, as well as of tangible product modularity in proprietary hardware, is widely acknowledged. Nevertheless, modularity in open-source hardware (OSH) remains under-researched. This article first describes qualitatively different types of modularity based on two OSH case studies and then quantifies each type of modularity, following a unified network-based approach. The results are discussed and compared within each case to test the 'mirroring hypothesis', and between cases to evaluate the impact of physical against intangible modularity types. The ultimate goal is to prompt a discussion into a wide but under-explored subset in OSH.